(untitled) (DARYAFT, 2023)
In Baluchistan, the inception of Urdu poetry was delayed compared to other major literary centers of Urdu. There are several important reasons for this, which, along with the unfamiliarity of this remote region with Urdu as a language, the unavailability of chronological links from a research point of view bears specific importance. According to the known facts, the first voice of Urdu poetry was Mulla Muhammad Hassan Brahui; even after him, this region’s poetic journey seems to have been divided into large time gaps. This paper presents an analytical study of Urdu Ghazal, which was created in Baluchistan until the establishment of Pakistan. These initial relics of Urdu Ghazal in Baluchistan are not more than practiced forms, so they mostly fail to present a high specimen of creativity. However, under the influence of this poetic capital, this tradition of Urdu Ghazal got strengthened here in Baluchistan, and afterward, through this route, high and unique features of Urdu Ghazal appeared here, which can be proudly compared to the overall Urdu Ghazal.